Gender-specific differences of interaction between cadmium exposure and obesity on prediabetes in the NHANES 2007–2012 population - Jiang, Fei; Zhi, Xueyuan; Xu, Miao; Li, Bingyan; Zhang, Zengli (Endocrine, 2018)
Purpose Data from National Health and Nutrition Examination Survey (NHANES) for the years 2007–2012 were used to evaluate the interactions of cadmium (Cd) exposure with being overweight/obesity on the risk of prediabetes among adults 20 years older. Methods A total of 3552 subjects were included in the analysis. Urinary cadmium levels (UCd) was used as a biomarker for long-term exposure to Cd. Additive interaction was estimated using relative excess risk due to interaction (RERI), attributable proportion due to interaction (AP) and synergy index (S). Results Following covariates adjustments, we found significant associations of UCd with higher prediabetes prevalence, and this association was more apparent in males (Q4 vs Q1: OR = 1.95, 95%CI: 1.34–2.84); while overweight/obesity was associated with prediabetes both in males and in females. Additionally, there was a significant interaction between Cd exposure and being overweight/obesity on prediabetes risk among males (RERI = 1.18, 95% CI: 0.42–1.93; AP = 0.35, 95% CI: 0.12–0.58; S = 2.00, 95% CI: 0.92–4.34). Conclusions Our results suggest that being overweight/obesity may substantially amplify the adverse effects of long-term cadmium exposure on prediabetes risk, and this interaction is more severe in male adults. Further studies are needed to confirm these findings.